posted by .

When you are decomposing fractions into constants


1/(x-1)(x-2)^2 = A/(x-1) + B/(x-2) + C/(x-2)^2

Why do you have to repeat (x-2), instead of just putting B/(x-2)^2?

I know how to solve these types of problems, but I don't understand it conceptually.

  • calculus -

    Suppose you had to add

    1/(x-1) + 1/(x-2) + 1/(x-2)^2

    your common denominator would be (x-1)(x-2)^2

    in the same way if you had

    1/(x-1) + 1/(x-2)^2
    you would still have that same common denominator of (x-1)(x-2)^2

    So when you are trying to reverse the process, how do you know which way it was?
    To allow for all possibilities we use the first version.
    In the first case, if the 2nd term is missing, that will show up as B=0

  • calculus -

    You could solve it as you put it:

    1/(x-1)(x-2)^2 = A/(x-1) + B/(x-2) + C/(x-2)^2

    or as
    1/(x-1)(x-2)^2 = A/(x-1)+(Bx+C)/(x-2)^2

    otherwise you'd be missing one parameter of type B/(x-2) in the most general form.

  • calculus -

    Wow that makes sense. Although, how come the C/(x-2)^2 doesn't follow the rule where the numerator must be one less power than the denominator?

    Shouldn't it be Cx+D/(x-2)^2?

  • calculus -

    When you have B/(x-2), it takes care of the term Bx/(x-2)^2, so you use either one of the two, preferably the former.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    I just don't understand this question: h(t)=A*b^x h(3)=4 h(5)=40 Solve for b Would you plug 3 into the x and set it equal to 4?
  2. Math

    how do i solve this: a over b divided by 11 over c = d over 6 I have to find out whaat the letters stand for --------------------------------------- questain for top: Give values a,b,c and d; to create your own division problom --------------------------------------- …
  3. math

    HELP. Help I have to decide whether these are rational or irrational. .73737373... .61611611161111..... 1/23 Can someone explain this to me?
  4. Calculus - Integrals

    I made this question, just wanted to make sure it didn't drown under the tide... I've set a problem up, something like this. s^4: A+D=0 s^3: -2A+B-3D+E=0 s^2: 2A-B+C+3D-3E=0 s^1: -2A+B-D+3E=4 s^0: A+C-E=4 Count Iblis -It's easier to …
  5. Math/Fractions

    I have this fraction: 6 2/9 + 1 3/4 - 3 5/6= Okay First I changed the mixed numbers into improper fractions. I got this: 56/9 + 7/4 + 23/6 Then I thought you have to find the least common denominator, which for 9,4, and 6 would be …
  6. math

    ACTIVITY 12: TERMINATE OR REPEAT? Every fraction has a decimal equivalent that either terminates (for example, ) or repeats (for example, ). Work with a group to discover which fractions have terminating decimals and which have repeating
  7. Calculus

    State the growth factor in each of the following situations. Newspaper readership is declining by 7 1/3 % per year. A bouncing ball rebounds to 1/3 of its previous height. Dont know how to solve these fractions:\ I just hate working …
  8. Mathematics

    Can someone explain to me how to solve complex fractions as if I didn't know anything about Algebra?
  9. Calculus

    Please check my answers. Solve the following equations and/or system of equations for the unknown variables. 1. x^2-3x-12=0 x= 3 + sqrt(57) / 2, x= 3 - sqrt(57) / 2 2. x+y=8 , 3x+2y=2 x=-14, y=22 3. 3x + 2y =10 , x+y=5 , y+z =9 x=0,y=5, …
  10. Math / Fractions

    I have 3 mixed fractions 2 1/4 , 1 1/2 , 3 5/8 Now I already turned them into improper fractions. 9/4 , 3/2 , 29/8 But I'm a little confused on how to get the common denominator.. Is it 8?

More Similar Questions